Evaluation of occupational burnout and related factors in industry managers - M. Sadaf; SA. Moravveji; HR. Saberi (Salāmat-i kār-i Īrān, 2008)
Background and aims   Occupational burnout is considered as side effects of occupational  stress. It includes some mental, functional, and personal characteristics in which a person has some symptoms of them. Occupational burnout can be caused in all jobs..it diminishes performance and utilization,   depression and disease. Due to the important role of managers, this study was carried to asses the  occupational burnout in industry managers in Kashan.   Methods   The industrial managers of Kashan at high managerial levels were enrolled in the  survey. Burnout data collected by standard questionnaire of Maslach Burnout Inventory (MBI) was then analyzed using SPSS-13 software and statistical methods of chi-square, t-test, ANOVA,   and regression analysis.   Results   Between 100 different industrial managers that were involved in this study, 90 persons responded to questionnaire, Include: 16 persons (17.8%) were employer,26 persons top manager(28.9%),36 persons (40%) middle-manager,12 persons (13.3%)high managers.97% were men and mean of age, work hours in week, work years duration respectly were 40.3(±8.26)years, 53.4(±20.6) hours, 15.7(±8.7) years. It seems that most people under study had  mild occupational burnout. sever occupational burnout was observed in emotional exhaustion(   3%in severity and10.9% in frequency)and depersonalization( 6.8%in severity and7.8% in  frequency).according to this study age, region, kind of management, month earn didn't relation with burnout . work years duration and number of workers had reveres relation with burnout . direct relation with burnout and work hours was founded.   Conclusion   Despite the low rate of moderate or severe burnout among the managers, further effort is advised to reduce stress in this group and probe them in psycho mental disorders.